THE GASTROPROTECTIVE EFFECT OF Bidens pilosa L. ETHANOL EXTRACT ON ALCOHOL-INDUCED GASTRIC ULCERS IN RATS: A HISTOPATHOLOGICAL STUDY - Situmorang, Elisa Rauli; Silitonga, Melva; Kurniawan, Rizal Eko (Universitas Syiah Kuala, 2025)
The primary objective of this research was to assess the gastroprotective properties of Bidens pilosa L. leaf ethanol extract by analyzing gastric histopathology in an alcohol-induced ulcer model in albino rats (Rattus norvegicus). The research was conducted experimentally using a completely randomized design involving five groups. The rats in K- group received 0.5% carboxymethyl cellulose (CMC), while the rats in the K+ group were given 30% alcohol. Groups P1, P2, and P3 received 30% alcohol combined with ethanol extract of Bidens pilosa at doses of 250, 500, and 750 mg/kg BW, respectively. Alcohol was administered orally at a dosage of 10 mL/kg BW for 43 consecutive days. The observed parameters included histopathological features of the gastric tissue, specifically mucosal erosion, inflammatory cell infiltration, and necrosis. The results demonstrated that the extract significantly reduced alcohol induced gastric tissue damage, as indicated by lower erosion scores and inflammatory cell infiltration (P 0.05). Necrosis was not observed in any group, including in the K+ group. In conclusion, Bidens pilosa extract possesses potential gastroprotective properties, likely mediated by anti-inflammatory and cytoprotective mechanisms.